Avaliação da associação das medidas de isolamento social na pandemia por Covid19 nas exacerbações em pneumopatas crônicos - Velasco, Flávia Castro (2022)
Objective: To assess the association between social isolation and the frequency of exacerbations in patients with chronic lung disease at the pulmonology outpatient clinics of the HC/UFG Methods: Observational, descriptive, cross-sectional study, in which patients from the hospital of the UFG clinics who were scheduled in the pulmonology outpatient clinics (COPD, asthma, pulmonary circulation, cystic fibrosis and bronchiectasis) from March to July 2020 were evaluated. Elective outpatient consultations were suspended in compliance with the social isolation measures defined by the Ministry of Health during the COVID-19 pandemic. The data collection questionnaires were filled out over the phone by the researcher with the call recorded. The data contained epidemiological assessment, characteristics of isolation, access to medication, exacerbations in the period evaluated and perception of symptoms. Results: In the evaluated period, 516 patients were scheduled, and 344 patients were excluded due to inability to access the telephone or inability to answer the research questionnaires, or refusal to participate, leaving 172 patients included in the study. The most prevalent diseases were asthma and COPD, 40.1% and 25.6% respectively, followed by pulmonary hypertension (16.9%), non-cystic fibrosis bronchiectasis (5.2%) and cystic fibrosis (4.7%). It was observed that the majority did not work outside the home (77%), and after social isolation there was a reduction in patients who worked outside the home (15%) compared to before isolation (23%). It is noticed that most people left the house less after the beginning of isolation (93%). Regarding the treatment, 80.2% had no difficulties in getting medications for continuous use. In physical activities, about half of the participants stopped exercising. It was observed that 117 patients (68%) had no exacerbation in the period. There was an association of exacerbation in patients who clarified doubts with a doctor (27.3%, p 0.01), who considered they were not well (69.1%, p < 0.01) and who rated more severe levels of dyspnea 2 -3 and 4-5; 61.8% and 18.2% (p<0.01) respectively. The absence of exacerbations was associated with the lowest rating of shortness of breath 0-1 (52.1%, p<0.01). Regarding the socio-demographic profile, life habits and risk factors, exacerbation was associated with black patients (21.8%, p=0.04) with no associations with other variables. Conclusions: Most of the participants avoided leaving the house during isolation, and 2/3 of the patients did not experience an exacerbation during the analyzed period. There was an association with exacerbation in patients who sought medical care and participants who reported worse symptoms and did not consider themselves to be well.